Effect of CMV and Aging on the Differential Expression of CD300a, CD161, T-bet, and Eomes on NK Cell Subsets - Lopez-Sejas, Nelson; Campos, Carmen; Hassouneh, Fakhri; Sanchez-Correa, Beatriz; Tarazona, Raquel; Pera, Alejandra; Solana, Rafael (Frontiers in Immunology, 2016)
Natural killer cells are innate lymphoid cells involved in the defence against virus-infected cells and tumour cells. NK cell phenotype and function is affected with age and CMV latent infection. Aging affects the frequency and phenotype of NK cells and CMV infection also contributes to these alterations. Thus, a reduction of CD56bright NK cell subpopulation associated with age and an expansion of memory-like NK cells CD56dimCD57+NKG2C+ probably related to CMV-seropositivity have been described. NK cells express T-bet and Eomes transcription factors that are necessary for the development of NK cells. Here we analyse the effect of age and CMV-seropositivity on the expression of CD300a and CD161 inhibitory receptors and T-bet and Eomes transcription factors in NK cell subsets defined by the expression of CD56 and CD57. CD300a is expressed by the majority of NK cells. CD56bright NK cells express higher levels of CD300a than CD56dim NK cells. An increase in the expression of CD300a was associated with age whereas a decreased expression of CD161 in CD56dim NK cells was associated with CMV-seropositivity. In CD56dim NK cells an increased percentage of CD57+CD300a+ and a reduction in the percentage of CD161+CD300a+ cells were found to be associated with CMV-seropositivity. Regarding T-bet and Eomes transcription factors, CMV-seropositivity was associated with a decrease of T-bethi in CD56dimCD57+ NK cells from young individuals whereas Eomes expression was increased with CMV-seropositivity in both CD56bright and CD56dimCD57+/− (from middle-age and young individuals, respectively) and was decreased with ageing in all NK subsets from the three group of age. In conclusion, CMV infection and age induce significant changes in the expression of CD300a and CD161 in NK cell subsets defined by the expression of CD56 and CD57. T-bet and Eomes are differentially expressed on NK cell subsets and their expression is affected by CMV latent infection and ageing.